2018
DOI: 10.1186/s13643-018-0743-4
|View full text |Cite
|
Sign up to set email alerts
|

Health technology assessment of public health interventions: an analysis of characteristics and comparison of methods—study protocol

Abstract: BackgroundConducting a health technology assessment (HTA) of public health interventions (PHIs) poses some challenges. PHIs are often complex interventions, which affect the number and degree of interactions of the aspects to be assessed. Randomized controlled trials on PHIs are rare as they are difficult to conduct because of ethical or feasibility issues.The aim of this study is to provide an overview of the methodological characteristics and to compare the applied assessment methods in HTAs on PHIs.MethodsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The detailed methods are presented in our protocol (11). As no outcome of direct patient or clinical relevance is assessed in this work, the protocol was not registered in PROSPERO.…”
Section: Objectivesmentioning
confidence: 99%
“…The detailed methods are presented in our protocol (11). As no outcome of direct patient or clinical relevance is assessed in this work, the protocol was not registered in PROSPERO.…”
Section: Objectivesmentioning
confidence: 99%
“…Reshaping the current public health HTA methods and related practices of policy priority setting will be crucial for implementing efficient and effective interventions. The quickly expanding use of the HTA concepts by professionals and stakeholders from different horizons holds great promise for ameliorations in PH-oriented research and strategies across the different scientific and policy territories in spite of the challenges this poses (13,(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review about HTAs of PH interventions reported a limited number of guidelines in this field. The authors also observed numerous, and often unjustified, changes to recommendations such as adaptations in the processes of quality evaluation, assessment of applicability, and integration of qualitative and quantitative evidence (12,13). These methodological tweaks were mainly linked to the fact that complex PH interventions implement diverse methodologies that often fall outside a controlled experimental setup such as those processed in randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%
“…The HTA of CIs is an emerging research area that is still fragmented, complex, broad, poorly understood, understudied or not researched in detail. 68 69 The scoping review represents the most suitable method for responding to the questions of the proposed study, as it aims to outline, map, synthesise and disseminate different concepts and types of evidence that exist around the conduct of HTA in relation to CIs, and identify the gaps for further research.…”
Section: Methods and Analysismentioning
confidence: 99%